C-reactive protein induces expression of matrix metalloproteinase-9: A possible link between inflammation and plaque rupture - Cimmino, Giovanni; Ragni, Massimo; Cirillo, Plinio; Petrillo, Gianluca; Loffredo, Francesco; Chiariello, Massimo; Gresele, Paolo; Falcinelli, Emanuela; Golino, Paolo (International journal of cardiology, 2013)
Matrix metalloproteases (MMPs) have been implicated in the pathogenesis of acute coronary syndromes (ACS). However, little is known about the mechanisms responsible for MMP expression in ACS. C-reactive protein (CRP) not only is an independent risk factor for cardiovascular events, but also may exert direct pro-atherosclerotic effects. Therefore, we aimed at determining whether CRP might induce MMP-9 in two different experimental conditions: 1) smooth muscle cells (SMCs) in vitro, and 2) patients with ACS. Effects of increasing concentrations of CRP on MMP-9 expression were evaluated in vitro in human SMCs. TIMP-1 protein expression, the selective inhibitor of MMP-9, was also evaluated. CRP dose-dependently induced MMP-9 expression in SMCs by promoting MMP-mRNA transcription, as well as MMP-9 secretion. In contrast, no differences were found for TIMP-1 protein expression. In vivo, MMP-9 and CRP levels were measured in blood samples obtained from the aorta (Ao) and the coronary sinus (Cs) of patients with normal coronary arteries (controls, n=21), stable angina (n=24), and ACS (n=30). Both MMP-9 and CRP plasma levels were significantly increased across the coronary circulation only in patients with ACS. Interestingly, a significant correlation between MMP-9 and CRP plasma levels was found. CRP induced MMP-9 expression and activity in human SMCs in culture; patients presenting with ACS have increased transcoronary plasma levels of MMP-9 and CRP with a significant correlation between these two markers. This may explain the heightened risk of coronary events in subjects with elevated levels of CRP.